PENGARUH E-SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN GO-JEK MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis UNISMA Pengguna Jasa Go-Jek) - Mochammad Zulkifli Fauzi; N Rachma; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purpose of this study is to find out and analyze the influence of e-service quality toward Go-Jek customers loyality through satisfaction as intervening variable with testing in every variable. Purpossive sampling was used to adopt the sample of this study which means using particular condsideration by paying attention toward respondents that is required in taking the sample. The setting of this study is in faculty of economic and bussiness of UNISMA especially the students who are active as the user of Gojek application. This study uses descriptive-quantitative annalysis by using asessment through likert scale which the whole results will be tested the validity,  the reliability,  the normality assumption,  the regretion annalysis, T testing and the path analysis.            From the result of data analysis, partially prove that e-service quality, loyality and satisfaction directly emerge positive and significant influence. While the result of indirect test shows that satisfaction can not mediate e-service quality and loyality. Because  even when the customers are not satisfy, they will keep using GoJek in the future time.Keywords : e- service, loyality , satisfaction